2002
DOI: 10.1002/gps.647
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and stress amongst old age psychiatrists

Abstract: SUMMARYObjective To investigate the relationship between work patterns, burnout and stress in consultant old age psychiatrists. Methods We sent a postal survey to all old age psychiatrists on the Faculty of Old Age Psychiatry, Royal College of Psychiatrists, list. Participants completed a workload questionnaire, the Stress Checklist and the Maslach Burnout Inventory during a specified week. Results Burnout scores were unaffected by gender and team working, but old age psychiatrists scoring within the high burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 16 publications
1
19
0
4
Order By: Relevance
“…And some studies reported no gender differences in burnout (e.g. Benbow and Gender differences 679 Jolley, 2002;Etzion, 1988;Greenglass, 1991;Hakanen, 1999;Izraeli, 1988;Maslach and Jackson, 1985).…”
mentioning
confidence: 99%
“…And some studies reported no gender differences in burnout (e.g. Benbow and Gender differences 679 Jolley, 2002;Etzion, 1988;Greenglass, 1991;Hakanen, 1999;Izraeli, 1988;Maslach and Jackson, 1985).…”
mentioning
confidence: 99%
“…Antonious and Cooper (2005) define stress as a form of emotion, an automatized response to the perception of threat. Researchers have noted that people's psychological reactions to the world around them can create wear and tear on their bodies that may eventually manifest themselves in physiological conditions such as high blood pressure, ulcers, headaches, and other health problems (Borg, 1990;Benbow & Jolley, 2002;Anshel, Sutarso & Jubenville, 2009). The conditions may also create, among others, psychological conditions of nervous tension and feelings of depression which affect an individual's well being (Sakharov & Farber, 1983;McCormick & Ilgen, 1985;Stumpfer & Banks, 1996, Child, 2007.…”
Section: Stress Health and Human Well-being 11mentioning
confidence: 99%
“…If a person perceives something as a danger, then the person will feel at harm. The perceived stress is a stressor, which then makes the individual feel stressed activating the changes in physiological responses (Benbow & Jolley, 2002;Child, 2007).…”
Section: Stress Health and Human Well-being 11mentioning
confidence: 99%
“…213,296,297 One study of CMHNs working in a broad range of CMHTs in Wales found evidence of greater burnout among those with an elderly caseload. 298 Existing evidence identifies a DOI: 10.3310/pgfar02040 PROGRAMME GRANTS FOR APPLIED RESEARCH 2014 VOL.…”
Section: Introductionmentioning
confidence: 99%